STUDI PROSES AGREGASI AIR DALAM BAHAN BAKAR DIESEL MENGGUNAKAN SIMULASI DINAMIKA MOLEKUL COARSE GRAIN - Khabib Khumaini; Mohammad Koyimatu; Tegar Nurwahyu Wijaya (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2019)
Presence of water in diesel can improve the combustion efficiency and reduce NOx and SOx emission. A small portion of non-ionic surfactants is required to prevent aggregation and separation water from diesel. Thus, coarse grain molecular dynamic simulation was conducted to study aggregation process of water in dodecane with absence and presence of non-ionic surfactants. The simulation was performed at 300 K and 1 atm using GROMACS 2016 with martini force field v2.2ref for 1500 ns. The analysis of simulation coordinate show that aggregation process occurred in both condition. However, the presence of non-ionic surfactants in surface of water aggregate prevents the aggregation process further. Hence, water aggregation in presence of surfactants is slower and incompleted. Furthermore, this method can be used to develop new non-ionic surfactants to stabilize water in diesel.